White‐Light Photoassisted Covalent Functionalization of Graphene Using 2‐Propanol. Issue 11 (12th October 2017) - Lundstedt, Anna; Papadakis, Raffaello; Li, Hu; Han, Yuanyuan; Jorner, Kjell; Bergman, Joakim; Leifer, Klaus; Grennberg, Helena; Ottosson, Henrik
Abstract: Herein, a photochemical method for functionalization of graphene using 2‐propanol is reported. The functionalization method which is catalyst‐free operates at ambient temperature in neat 2‐propanol under an inert atmosphere of argon. The equipment requirement is a white‐light source for the irradiation. The same methodology when applied to kish graphite results in a novel material, exhibiting significantly higher wettability than the starting material according to water contact angle measurements. Furthermore, the materials generated from both graphene and kish graphite exhibit increased adhesion energy, attributed to the fixation of isopropyl alcohol fragments onto graphene and graphite, respectively. The presence of hydroxyl groups and the possibility for further reactions on the functionalized graphene material are demonstrated through a substitution reaction with thionyl chloride, where the hydroxyl groups are replaced with chlorides, as confirmed through X‐ray photoelectron spectroscopy analysis. Abstract : A novel covalent functionalization of graphene under metal‐free conditions using merely white‐light irradiation and 2‐propanol is reported. The material obtained is characterized by high adhesion energy. When the same methodology is applied to graphite, the resulting material exhibits a substantially higher wettability than the parent material. In this way, a shining future for the functionalization of graphene is expected.